The Impact of Multi-Culture on International Business - Christopher, Iriowen (Vilnius University Proceedings, 2023)
Migration of populations from various backgrounds and cultures is an important feature of globalisation and the development of global society. Migration, free labour movement, and the cultural diversity they generate have all become significant components of current global economic theory and demographic growth. They stress the importance of coexistence and collaboration among different ethnicities, countries, and cultures. As many Western cultures experience declining working-age populations, the solution appears to be in the hiring of immigrants and foreigners. However, this results in a clash of cultures, beliefs, and fundamental societal ideals. It is consequently critical to recognise and grasp the nuances that exist in multicultural corporate environments, as well as to benefit from the managerial techniques that emerge in those environments. Multicultural and diversity management can thus become a useful instrument for boosting the efficacy of international business practices and, as a result, become more widely adopted.
Keywords: culture; impact; multiculturalism; international market